Assessing the correlation of microscopy‐based and volumetry‐based measurements for resin swelling in a range of potential greener solvents for SPPS. (25th March 2020) - Magtaan, Jordan Kevin; Devocelle, Marc; Kelleher, Fintan
Abstract : The degree of resin swelling in a particular solvent system is one of the critical parameters for solid‐phase peptide synthesis (SPPS) and for solid‐phase synthesis in general. Methods used for measuring the degree of resin swelling include microscopy‐based and volumetry‐based methods. This study describes and compares the use of both methods for a number of commercially available resins commonly used in SPPS, with a range of solvents, which have been identified in the literature as 'greener' than DCM, DMF and NMP. The results were analysed by statistical methods, and a significant correlation between the two distinct methods has been demonstrated for the first time. The results will likely be used, in conjunction with other literature methods, to help in choosing both the resin and solvent system for greener SPPS, as well as for continuous flow SPPS, which is of growing importance. Abstract : A strong correlation exists between volumetric and microscopic methods of measuring resin swelling in organic solvents.